Strategic customer management : integrating relationship marketing and CRM - Payne, Adrian; Frow, Pennie (Cambridge : Cambridge University Press, 2013)
Relationship marketing and customer relationship management (CRM) can be jointly utilised to provide a clear roadmap to excellence in customer management: this is the first textbook to demonstrate how it can be done. Written by two acclaimed experts in the field, it shows how an holistic approach to managing relationships with customers and other key stakeholders leads to increased shareholder value. Taking a practical, step-by-step approach, the authors explain the principles of relationship marketing, apply them to the development of a CRM strategy and discuss key implementation issues. Its up-to-date coverage includes the latest developments in digital marketing and the use of social media. Topical examples and case studies from around the world connect theory with global practice, making this an ideal text for both students and practitioners keen to keep abreast of changes in this fast-moving field.
Introduction -- Relationship marketing -- Customer relationship management: Key processes -- Strategic customer management implementation.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Customer relations -- Management